Elliptical Fourier analysis of molar outlines in Late Pliocene Parapapio whitei from Makapansgat Limeworks, South Africa - Kim, Alexander C.; Williams, Frank L’Engle (Anthropological Review, 2024)
Introduction: Alongside Australopithecus africanus at Makapansgat South Africa, dated to nearly 3 million years before present, are remnants of Parapapio (Cercopithecinae). The extreme variability of this fossil assemblage has stymied efforts to specify the taxon parameters for Parapapio, which are attributed to at least three species. Study aims: The first maxillary molar occlusal outlines of the two most complete fossils attributed to Parapapio whitei are compared. The degree of group cohesion in Parapapio whitei is evaluated using three extant cercopithecoid taxa. Methods and Materials: The fossil crania from Makapangsat Members 3–4, MP 221 and MP 223, both referred to Parapapio whitei, are compared to three extant cercopithecoid taxa including Cercocebus agilis (n=8), Colobus angolensis (n=8) and Papio anubis (n=8). Molar shape is captured using elliptical Fourier analysis of occlusal outlines and molar size dimensions are estimated from measuring software. Results: MP 223 is larger than MP 221 in occlusal area and the minimum buccolingual length of M1 although the variability between the two Parapapio whitei fossils is commensurate with that observed in Papio anubis. MP 221 and MP 223 are more similar to one another in occlusal outline shape than to any other taxon. However, MP 223 falls consistently closer to Papio anubis whereas MP 221 resembles Papio anubis in some respects and Cercocebus agilis in others. Conclusion: MP 221 and MP 223 likely belong to a single species with no clear affinity to any of the extant taxa examined. The differences in molar size characterizing Parapapio whitei, a terrestrial forager, is potentially indicative of male bimaturatism or ecological variability which may also characterize Australopithecus africanus at Makapansgat.